2010
DOI: 10.1002/clc.20801
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Corrected QT Interval Following Liver Transplant in Patients With End‐Stage Liver Disease

Abstract: Background: Studies have demonstrated that patients with end-stage liver disease (ESLD) often have a prolonged corrected QT interval (QTc) with variable changes in the QTc post-transplant. We sought to characterize the prevalence and degree of QTc prolongation in ESLD patients, identify risk factors for QTc prolongation, and assess changes in QTc following transplant. Hypothesis: QTc interval is prolonged in ESLD patients pre-transplant due to a variety of risk factors and shortens following liver transplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 47 publications
(38 reference statements)
2
19
0
Order By: Relevance
“…Although QTc prolongation is common in patients with ESLD, it often resolves after transplantation (93,94). In a retrospective cohort, nearly one-half of 600 ESLD patients studied had a QTc Ͼ440 ms pre-operatively, with resolution in approximately one-half of these patients after transplantation.…”
Section: Qt Interval Prolongationmentioning
confidence: 98%
“…Although QTc prolongation is common in patients with ESLD, it often resolves after transplantation (93,94). In a retrospective cohort, nearly one-half of 600 ESLD patients studied had a QTc Ͼ440 ms pre-operatively, with resolution in approximately one-half of these patients after transplantation.…”
Section: Qt Interval Prolongationmentioning
confidence: 98%
“…Five studies assessing post-transplant outcomes did not show impact of prolonged QTc on post-transplant survival. (4,5,7,9,10) However, Sonny et al (11) showed that composite outcomes denoted by mortality, graft failure, and/or major cardiovascular events (CVEs) were associated with prolonged QTc pretransplant during a mean follow-up of 5 years post-transplant. Major CVEs were defined as the presence of coronary artery disease requiring intervention, congestive heart failure (HF), or ischemic stroke.…”
Section: Impact Of Qtc Changes On Post-transplant Coursementioning
confidence: 99%
“…This was attributed to vagal reactivation post-exercise which was similar vs. baseline, especially in the time domain RMSSD and SDNN and in frequency domain HFnu, considered parameters of parasympathetic modulation [33]. Previous studies reported electrophysiological abnormalities with repolarization change in patients with liver cirrhosis, attributed to alterations in the potassium channels, worsening with the disease condition [8,38]. Alterations in the cardiovascular function with hyperdynamic circulation, reduced systolic contraction and diastolic relaxation can increase the sympathetic modulation in order to maintain the cardiac output in these patients [31,36].…”
Section: Discussionmentioning
confidence: 99%